Progressing in the change journey towards sustainability in healthcare: the role of 'Green' HRM. (20th May 2016) - Pinzone, Marta; Guerci, Marco; Lettieri, Emanuele; Redman, Tom
Abstract: This study is the first that theorises and empirically tests, at the organisational level, the role that 'Green' Human Resource Management (HRM) practices play in facilitating employees' collective engagement in environment protection by taking voluntary actions that 'go the extra mile'. In this regard, we take an original perspective on Environmental Management (EM) as an organisational change that requires strong support from employees. This allows us to investigate the mediating role of collective commitment to change – and specifically to EM – with regard to the relationship between 'Green' HRM practices and collective voluntary behaviours towards the environment. Our results show that 'Green' HRM practices are conducive to voluntary behaviours towards the environment at the collective level. Moreover, employees' willingness to support their organisation in its EM endeavour partially mediates this relationship. Additionally, by conceptualising three different types of 'Green' HRM practices, our results disentangle their relative importance and their differing impact on collective behaviours towards the environment. This paper thus provides scholars of EM and managers with original evidence-based guidelines on how to leverage 'Green' HRM to enhance employees' collective attitudes and behaviours towards the environment. Highlights: The link between 'Green' HRM practices and collective OCBEs is analysed. The mediating role of collective Affective Commitment to EM change is examined. A survey of organisations within the English National Health System is reported. Results support 'Green' HRM practices being positively associated with collective OCBEs. Partial mediation by collective Affective Commitment to EM change is supported.